Rohr, Yolande of Aragon (1381-1442) Family and Power: The Reverse of the Tapestry (Palgrave Macmillan, 2015) - Derek R Whaley (Royal Studies Journal, 2016)
Review of Zita Eva Rohr, Yolande of Aragon (1381-1442) Family and Power: The Reverse of the Tapestry (New York: Palgrave Macmillan, 2015).